Goodvertising creative advertising that cares - Kolster, Thomas (New York, New York Thames & Hudson Inc., 2012)
Can advertising be a force for good? Can it bring about positive social or environmental change? Should it tell the truth about a brand?

Today's consumers are more informed, empowered and ethically minded than ever. No longer can an agency simply state that their client's brand or product is good: the advertising has to communicate that the client is actively doing good.

Goodvertising showcases outstanding creative work in more than 120 campaigns from around the world. Each campaign is from a leading agency working in the full spectrum of media channels for an international array of clients, be they corporations or charities. For any advertising or branding professional, this timely book will provide inspiration and insights: proof positive of the power of advertising for good.
Transparency -- Connection -- Simplicity -- Collaboration -- Compassion -- Creativity -- Contagiousness -- Generosity -- Insight -- Positivity -- Commitment.
Includes bibliographical references and index.
Donated by Prof. Michelle Roxas
Keywords: Advertising; Commercial art -- Technique